Oral semaglutide versus subcutaneous liraglutide and placebo in type 2 diabetes (PIONEER 4): a randomised, double-blind, phase 3a trial. Issue 10192 (6th July 2019) - Pratley, Richard; Amod, Aslam; Hoff, Søren Tetens; Kadowaki, Takashi; Lingvay, Ildiko; Nauck, Michael; Pedersen, Karen Boje; Saugstrup, Trine; Meier, Juris J
Summary: Background: Glucagon-like peptide-1 (GLP-1) receptor agonists are effective treatments for type 2 diabetes, lowering glycated haemoglobin (HbA1c ) and weight, but are currently only approved for use as subcutaneous injections. Oral semaglutide, a novel GLP-1 agonist, was compared with subcutaneous liraglutide and placebo in patients with type 2 diabetes. Methods: In this randomised, double-blind, double-dummy, phase 3a trial, we recruited patients with type 2 diabetes from 100 sites in 12 countries. Eligible patients were aged 18 years or older, with HbA1c of 7·0–9·5% (53–80·3 mmol/mol), on a stable dose of metformin (≥1500 mg or maximum tolerated) with or without a sodium-glucose co-transporter-2 inhibitor. Participants were randomly assigned (2:2:1) with an interactive web-response system and stratified by background glucose-lowering medication and country of origin, to once-daily oral semaglutide (dose escalated to 14 mg), once-daily subcutaneous liraglutide (dose escalated to 1·8 mg), or placebo for 52 weeks. Two estimands were defined: treatment policy (regardless of study drug discontinuation or rescue medication) and trial product (assumed all participants were on study drug without rescue medication) in all participants who were randomly assigned. The treatment policy estimand was the primary estimand. The primary endpoint was change from baseline to week 26 in HbA1c (oral semaglutide superiority vs placebo and non-inferiority [margin: 0·4%] and superiority vs subcutaneous liraglutide) and the confirmatory secondary endpoint was change from baseline to week 26 in bodyweight (oral semaglutide superiority vs placebo and liraglutide). Safety was assessed in all participants who received at least one dose of study drug. This trial is registered onClinicaltrials.gov, numberNCT02863419, and the European Clinical Trials registry, number EudraCT 2015-005210-30. Findings: Between Aug 10, 2016, and Feb 7, 2017, 950 patients were screened, of whom 711 were eligible and randomly assigned to oral semaglutide (n=285), subcutaneous liraglutide (n=284), or placebo (n=142). 341 (48%) of 711 participants were female and the mean age was 56 years (SD 10). All participants were given at least one dose of study drug, and 277 (97%) participants in the oral semaglutide group, 274 (96%) in the liraglutide group, and 134 (94%) in the placebo group completed the 52-week trial period. Mean change from baseline in HbA1c at week 26 was −1·2% (SE 0·1) with oral semaglutide, −1·1% (SE 0·1) with subcutaneous liraglutide, and −0·2% (SE 0·1) with placebo. Oral semaglutide was non-inferior to subcutaneous liraglutide in decreasing HbA1c (estimated treatment difference [ETD] −0·1%, 95% CI −0·3 to 0·0; p<0·0001) and superior to placebo (ETD −1·1%, −1·2 to −0·9; p<0·0001) by use of the treatment policy estimand. By use of the trial product estimand, oral semaglutide had significantly greater decreases in HbA1c than both subcutaneous liraglutide (ETD −0·2%, 95% CI −0·3 to −0·1; p=0·0056) and placebo (ETD −1·2%, −1·4 to −1·0; p<0·0001) at week 26. Oral semaglutide resulted in superior weight loss (−4·4 kg [SE 0·2]) compared with liraglutide (−3·1 kg [SE 0·2]; ETD −1·2 kg, 95% CI −1·9 to −0·6; p=0·0003) and placebo (−0·5 kg [SE 0·3]; ETD −3·8 kg, −4·7 to −3·0; p<0·0001) at week 26 (treatment policy). By use of the trial product estimand, weight loss at week 26 was significantly greater with oral semaglutide than with subcutaneous liraglutide (−1·5 kg, 95% CI −2·2 to −0·9; p<0·0001) and placebo (ETD −4·0 kg, −4·8 to −3·2; p<0·0001). Adverse events were more frequent with oral semaglutide (n=229 [80%]) and subcutaneous liraglutide (n=211 [74%]) than with placebo (n=95 [67%]). Interpretation: Oral semaglutide was non-inferior to subcutaneous liraglutide and superior to placebo in decreasing HbA1c, and superior in decreasing bodyweight compared with both liraglutide and placebo at week 26. Safety and tolerability of oral semaglutide were similar to subcutaneous liraglutide. Use of oral semaglutide could potentially lead to earlier initiation of GLP-1 receptor agonist therapy in the diabetes treatment continuum of care. Funding: Novo Nordisk A/S.